Land use changes and estimates of anthropogenic CO2 emissions in a watershed - Sousa, Jocy Ana Paixão De [UNESP]; Lopes, Elfany Reis Do Nascimento; Souza, José Carlos De; Lourenço, Roberto Wagner [UNESP] (Editora da Universidade Federal de Uberlândia - EDUFU, 2022)
Anthropogenic interference has always impacted the Earth's surface, with greater intensity in recent times due to land use changes, which contribute to the emission of greenhouse gases, especially carbon dioxide. In this sense, this study analyzes land use transitions and CO2 emissions resulting from these actions in a watershed. For this, land use mappings were made in 2007, 2010, 2013, and 2016, along with estimates of the emissions from transitions. The calculation of net CO2 emissions included data from the transitions that occurred, from past vegetation, and pedological information. All procedures were performed with the aid of geoprocessing and remote sensing techniques, resulting in matrices of transitions and CO2 emissions, in addition to spatialized information. The forest category showed the highest conversion to other types of land use, with a loss of 208.86 ha between 2010 and 2013. In the observed period of nine years, carbon emissions were higher than its sequestration from the atmosphere, which shows the need for management and planning to mitigate the impacts caused by intense land use changes in the studied watershed.
Keywords: Greenhouse gases; Environmental impacts; Transition matrix